The Role of Local Government in the Implementation of Social Assistance for the Eradication of Extreme Poverty in the Meranti Islands Regency - Rahyunir, Muhammad Hafizh; Zulherawan, M. (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Various social assistance programs implemented by the government in Kepulauan Meranti Regency, such as the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), Rice Food Assistance, Direct Cash Assistance (BLT), Health Insurance Contribution Assistance (JKN Contribution Assistance), and Housing Assistance for Uninhabitable Homes (Bansos RTLH), are part of a strategic effort to accelerate the eradication of extreme poverty. The evaluation of the implementation of these programs shows that the success of eradicating extreme poverty largely depends on accurate targeting, smooth distribution, integration across programs, and active involvement of the local government in supervision and guidance. With continuous improvements in beneficiary data accuracy, program integration, and the empowerment of local communities, the overarching goal of achieving an extreme poverty-free Kepulauan Meranti Regency can be reached more swiftly. The purpose of this study is to identify and analyze the evaluation of the Social Assistance Program for Accelerating the Eradication of Extreme Poverty in Kepulauan Meranti Regency. This research uses a qualitative approach. The informants in this study consisted of 7 individuals, with the Secretary of the Regional Development Planning, Research, and Development Agency (Bappedalitbang) of Kepulauan Meranti Regency serving as the key informant. Data collection was carried out through interviews, and data analysis employed triangulation techniques. Based on the research findings, it is concluded that the evaluation of the Social Assistance Program for Accelerating the Eradication of Extreme Poverty in Kepulauan Meranti Regency indicates that while this program does indeed provide positive impacts for its beneficiaries, there remain several challenges that need to be promptly addressed to ensure optimal program implementation. Overall, the program represents a well- conceived strategic step toward the acceleration of extreme poverty eradication, but it still requires improvements in many aspects, particularly in data updating, enhanced coordination, and efficiency in the distribution of assistance.